Decolonizing the Boundaries between the 'Planner' and the 'Planned': Implications of Indigenous Property Development. (26th May 2020) - Barry, Janice; Thompson-Fawcett, Michelle
ABSTRACT: This paper examines Indigenous property development, drawing on research into the development of treaty settlement lands in Manitoba, Canada, and Canterbury, New Zealand. It highlights two contradicting ways of understanding this work: Indigenous peoples as self-determining, with authority to develop their own urban planning approaches, and Indigenous peoples as conventional property developers, subject to the same rules as any other private interest. This contradiction is used to expose a need for alternative, decolonial ways of understanding relationships between the 'planner' and the 'planned', grounded in the recognition of overlapping governance roles and responsibilities which Indigenous peoples are now (re)claiming in the urban environment.